Are Public Banks pro-Competitive? Evidence from Concentrated Local Markets in Brazil - Christiano A. Coelho; Jo\~ao Manoel Pinho de Mello; Leonardo Rezende (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2007)
We measure the competitive effect of public ownership of banks in concentrated local banking markets in Brazil by extending Bresnahan and Reiss's [1991] framework to measure the effects of entry in concentrated markets. We use variation in market size, the number of competitors and their identity to infer how conduct is affected by the entry of a private vis-à-vis a public bank. We find that, while local markets whose structure is private bank duopoly are 100% larger than private monopolies, duopolies with one public and one private bank and private monopolies are no different with respect to market size. These results suggest that, while the presence of private banks toughens competition, public banks do not affect conduct.
Keywords: L10; L13; L33; 330; banking industry; public versus private ownership; effect of entry.; Öffentliche Bank; Regionaler Finanzsektor; Wettbewerb; Brasilien